Hubungan Antara Motivasi Ibu Dengan Kunjungan Balita Ke Posyandu Di Dsn. Belahan Wilayah Kerja Puskesmas Puri - Zainuri, Imam (Jurnal Keperawatan Bina Sehat, 2012)
ABSTRACTPosyandu which is a community activity will lead to societys commitment especially the mothers, in preserving life and child growth, with technology experts from the government. The success key of Posyandu development Program is the growth society participation. The purpose of this study is to analyze the correlation between mothers motivation with the visit of toddlers to Posyandu in Dusun Belahan Brayung The Working Area of Puskesmas Puri Mojokerto Regency. The Design of this study is cross sectional analytic study design. The Population is all mothers who have toddlers as many as 88 people and taken 41 people as samples using purposive sampling. The variable is mothers’ motivation and toddlers’ visit. Data were collected using a Likert scale questionnaire on 17 May-19 May 2012. Collecting the data, did editing, coding, scoring, tabulating and analyzing data (univariate and bivariate statistical tests and Spearmans rho). Results showed that most of the respondents have low motivation as many as 22 respondents (53.7%) and unregularly toddlers’ visit of 22 respondents (53.7%). Based on Spearmans rho test obtained p value (0.000) < α (0.05), means that H0 is rejected, so there is a correlation between mothers motivation with the visit of toddlers to Posyandu in Dusun Belahan Brayung The Working Area of Puskesmas Puri Mojokerto Regency. The value of r = 0.573 and shows the medium relationship and positively correlated, means that the higher the mothers motivation, the higher their visit to Posyandu. The majority of respondents have low motivation and the toddlers’ visit to Posyandu is not regular. This may affected by age, occupation, education, and information resources. Should there be an effort to motivate mother to visit Posyandu regularly.Key words: motivation, toddlers, visit and posyandu